ANALYSIS THE NUMBER OF DEMAND AND EXPECTATIONS OF TOURISTS TOWARDS KLATEN TOURISM BUSS (CASE STUDY AT UMBUL PONGGOK) - Nur Jae Priyatna; Hera Widyastuti (Fakultas Pariwisata Universitas Pancasila, 2021)
Tourists who go to Umbul Ponggok choose to use private or rent vehicles, just because tourism transportation is not yet available. This condition opens opportunities for the need for tourism transportation, especially those that go to the Umbul Ponggok tourist attraction and later to other tourism objects that might be integrated. This research was conducted to analyze the demand for tourism transportation which is expected to be an alternative for tourism infrastructure in Umbul Ponggok in particular and other tourism in Klaten City in general. The data collection method is done by giving questionnaires to Umbul Ponggok tourists which is also the primary data. In addition, the existing tourists are assumed to be potential users of the tourism bus later. Secondary data used are data on visitors to Umbul Ponggok from the Office of Culture, Tourism, Youth and Sports (Disbudparpora) Klaten. The results obtained from the binary logistic regression model probability analysis show the number of tourism bus transportation demand based on the survey results as much as 78% (78 respondents out of 100 tourists) expect and welcome tourism transportation. This condition is also influenced by the independent variable of the Umbul Tourism Performance Level of 95.58%. Next is the expectations of tourists, the most important thing according to Umbul Ponggok visitors is the speed of the officers in serving the swimming equipment rental with an average expectation value of 4.19.